Functional remodeling of an electrospun polydimethylsiloxane‐based polyether urethane external vein graft support device in an ovine model. Issue 10 (27th May 2019) - El‐Kurdi, Mohammed; Soletti, Lorenzo; McGrath, Jonathan; Linhares, Stephen; Rousselle, Serge; Greisler, Howard; Edelman, Elazer; Schoen, Frederick J.
Abstract: Saphenous vein graft (SVG) failure rates are unacceptably high, and external mechanical support may improve patency. We studied the histologic remodeling of a conformal, electrospun, polydimethylsiloxane‐based polyether urethane external support device for SVGs and evaluated graft structural evolution in adult sheep to 2 years. All sheep ( N = 19) survived to their intended timepoints, and angiography showed device‐treated SVG geometric stability over time (30, 90, 180, 365, or 730 days), with an aggregated graft patency rate of 92%. There was minimal inflammation associated with the device material at all timepoints. By 180 days, treated SVG remodeling was characterized by minimal/nonprogressive intimal hyperplasia; polymer fragmentation and integration; as well as the development of a neointima, and a confluent endothelium. By 1‐year, the graft developed a media‐like layer by remodeling the neointima, and elastic fibers formed well‐defined structures that subtended the neo‐medial layer of the remodeled SVG. Immunohistochemistry showed that this neo‐media was populated with smooth muscle cells, and the intima was lined with endothelial cells. These data suggest that treated SVGs were structurally remodeled by 180 days, and developed arterial‐like features by 1 year, which continued to mature to 2 years. Device‐treated SVGs remodeled into arterial‐like conduits with stable long‐term performance as arterial grafts in adult sheep.